Pelvic Sonographic Findings, Their Relationship with Microorganisms Detected on Endocervical Swabs and Factors Associated with Sonographic PID among Women at Gynaecology Clinic of Mbarara Regional Referral Hospital - Peter, Masinde; Moses, Acan; Kenneth, Mworozi; Kennedy, Kassaza (EAS Journal of Radiology and Imaging Technology, 2024)
Aim: To study Pelvic sonographic findings, their relationship with microorganisms detected on endocervical swabs and factors associated with sonographic PID among women at Gynaecology clinic of Mbarara Regional Referral Hospital. Methods: 144 women aged 15-49 years with clinical diagnosis of PID at gynaecology clinic of MRRH were interviewed with structured questionnaires about socio-demographic, behavioural and gynaecological factors. Pelvic sonographic examination via transvaginal and transabdominal methods was performed. Analysis of sonographic PID findings, association with factors above and testing for gonorrhea and chlamydia by nucleic acid amplification test (NAAT), a DNA-PCR test was done. Data was entered using EPI info, exported to excel and analysed using STATA© 15.0 software (College Station, Texas, USA). Categorical variables were summarized as frequencies, percentages, Chi-square test followed by logistic regression. Continuous variables were summarized as mean and standard deviation. A factor was considered associated if p≤ 0.05. Results: Sonographic PID was diagnosed in 41.66% (60/144) of patients. Most presented with uterine findings 9.72% (14), free fluid in posterior cul-de-sac 6.94% (10). Few had fallopian tubal and ovarian findings each at 3.47% (5) respectively. However, most patients presented with mixed structural findings 18.05% (26). The rest of the patients 58.35% (84) had normal findings. Women with history of STIs [AOR = 2.8 (95% CI: 1.00–7.57), p=0.05] or had adnexal mass [AOR = 7.1 (95% CI: 1.58–31.90), p=0.01] were statistically more likely to have sonographic PID. Of the 144 women, 29.17% (42) were diagnosed with microorganisms, 22.92% (33) positive for Neisseria, 4.86% (7) positive for chlamydia and 1.39% (2) for both. However, at 5% level of significance diagnosis with Neisseria gonorrhoeae was associated with a higher likelihood of sonographic PID compared to absence of microorganisms (p<0.05). Conclusion: A high proportion of women with clinical diagnosis of PID at Gynaecology clinic of MRRH have pelvic sonographic PID findings. Patients who had history of STI and/or palpable adnexal mass were more likely associated with sonographic PID. Neisseria positive conferred a high likelihood of sonographic PID compared to absence of microorganisms.
Keywords: PID; Sonographic; Pelvic; Findings; Microorganisms